Małżeństwo zawrzesz poprzez złożenie formularza, w tej samej formie się rozwiedziesz : Recenzja pozycji „Instytucja małżeństwa w prawie japońskim. Problematyka zawarcia i ustania związku małżeńskiego” - Szklarczyk, Paweł (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
The author of the review has been researching issues related to Japanese statehood and law for several years. While reviewing the work by Barbara Jelonek, he wishes to emphasize the qualities of the said book, while at the same time criticizing some slight inaccuracies and omissions contained in it. For there has been no comprehensive book on the institution of marriage in Japanese law in Polish legal research so far, B. Jelonek's work is of a pioneering nature. It exhaustively introduces to legal, as well as historical, social and cultural aspects of marriage in Japan. In her work, the Author proves that the said institution was and (sadly) still is discriminatory against women.
Keywords: marriage; Japan; divorce; sex equality